Implementasi Metode Person In Charge (PIC) dan Monitoring Analisis Kurva– S untuk Percepatan Pengadaan Barang dan Jasa Pembangunan Kabel Laut 150 KV Landing Point Batulicin Kalimantan Selatan - mikky noperina citra; Dhami Johar Dhamiri (Energi & Kelistrikan, 2020)
ABSTRACT Achievement of the performance of the 2017 contract target of PT PLN (Persero) Central Kalimantan UIP, namely 54 contracted procurement packages and in 2018 there were 57 procurement targets with a temporary budget ceiling of Rp. 1,501,933,269,600.00. So as to achieve the 2018 contracted procurement target it will have an impact on the achievement of the 2019 Commercial Operation Date (COD) efforts needed to accelerate the implementation of goods and services. One of the basic knowledge (common knowledge) for acceleration in a knowledge management construction starts from adding three elements, including: labor, equipment, and overtime / overtime. After a Root Cause Problem Solver (RCPS) and priority scale selection process are carried out, two priority Problem Solving results have never been implemented as an effort to accelerate implementation, namely Parallel Work with Person In Charge (PIC) Method and Monitoring of Procurement Implementation Schedules with S-Curve Analysis . Keywords:Contracted, Person In Charge (PIC), Package, IDR (Rupiah).